KUALITAS PENYELENGGARAAN PELAYANAN PUBLIK (STUDI TENTANG KUALITAS PELAYANAN JASA TRANSPORTASI di STASIUN WONOKROMO SURABAYA) - Wahyuni, Rina Dwi (JPAP: Jurnal Penelitian Administrasi Publik, 2017)
This research entitled Quality Organization of Public Service (Study About Quality Service Transportation Services at Wonokromo Station Surabaya). This study aims to determine the quality of service at Wonokromo station. This research is descriptive using qualitative. Technique of data collection is done by observation, interview, and documentation. The research informants in this study are Head Station Wonokromo, Kasubur CC Station Wonokromo and passenger Station Wonokromo. From the results of the research can be seen that the service quality is considered good. The result of this research is connecting from Parasuraman theory that is from Direct Evidence dimension, Reliability, Responsiveness, Guarantee, and Empathy. Keywords : Quality of Service, Public Servuce, Qualitative